Improved global cropland data as an essential ingredient for food security - See, Linda; Fritz, Steffen; You, Liangzhi; Ramankutty, R.; Herrero, Mario; Justice, Chris; Becker-Reshef, Inbal; Thornton, Philip K.; Erb, Karlheinz; Gong, Peng; Tang, H.; Velde, Marijn van der; et al. (Elsevier, 2015)
Lack of accurate maps on the extent of global cropland, and particularly the spatial distribution of major crop types, hampers policy and strategic investment and could potentially impede efforts to improve food security in an environment characterized by continued market volatility and a changing climate. Here we discuss the pressing need for the provision of spatially explicit cropland datasets at a global scale and review the strengths and weaknesses of the various approaches used to develop such data.